2017
DOI: 10.1016/j.neuropharm.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase activation enhances object recognition memory in mice through phosphorylation of the extracellular signal-regulated kinase in the cortex and the hippocampus

Abstract: Rats injected with by d-phenylalanine, a carbonic anhydrase (CA) activator, enhanced spatial learning, whereas rats given acetazolamide, a CA inhibitor, exhibited impairments of fear memory consolidation. However, the related mechanisms are unclear. We investigated if CAs are involved in a non-spatial recognition memory task assessed using the object recognition test (ORT). Systemic administration of acetazolamide to male CD1 mice caused amnesia in the ORT and reduced CA activity in brain homogenates, while tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 44 publications
(66 reference statements)
2
78
0
Order By: Relevance
“…The lack of effect of ZIP in ORM consolidation does not mean that the hippocampus does not participate in this process. Although it is true that, based mainly on lesion studies, it has previously been suggested that the involvement of the hippocampus in ORM is restricted to the processing of spatial and contextual information instead of recognition memory per se (Ainge et al, 2006), it has lately become clear that this region is critical for ORM consolidation even when all spatial and contextual compo-nents of the task are omitted (Liu et al, 2016;Stackman et al, 2016;Canto de Souza et al, 2017;Cercato et al, 2016;Lymer et al, 2017). This is particularly evident when rodents are exposed to two identical or two different but behaviorally equivalent objects in a familiar open-field arena.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effect of ZIP in ORM consolidation does not mean that the hippocampus does not participate in this process. Although it is true that, based mainly on lesion studies, it has previously been suggested that the involvement of the hippocampus in ORM is restricted to the processing of spatial and contextual information instead of recognition memory per se (Ainge et al, 2006), it has lately become clear that this region is critical for ORM consolidation even when all spatial and contextual compo-nents of the task are omitted (Liu et al, 2016;Stackman et al, 2016;Canto de Souza et al, 2017;Cercato et al, 2016;Lymer et al, 2017). This is particularly evident when rodents are exposed to two identical or two different but behaviorally equivalent objects in a familiar open-field arena.…”
Section: Discussionmentioning
confidence: 99%
“…While results of the present study suggest that inhibition of carbonic anhydrase activity may enhance cognition, pharmacologic evidence to date has supported the opposite conclusion. Specifically, carbonic anhydrase activation has shown enhancement in synaptic efficacy, spatial learning, memory, as well as object recognition in rodents 74,78 ; in humans, topiramate, a carbonic anhydrase inhibitor has been associated with cognitive deterioration 79 . One mechanism by which carbonic anhydrase inhibition might improve cognitive function is in the context of amyloid pathology, which may be dependent on carbonic anhydrase activity.…”
Section: Discussionmentioning
confidence: 99%
“…CA activation was reported in an early stage of CA research, but the field remained highly controversial till recently, when work with highly purified enzymes and very precise techniques, such as the stopped-flow assay, undoubtedly demonstrated that the CA activators (CAAs) exist and that they take part to the catalytic cycle [49][50][51][52][53]. However, up until recently there seem to be no pharmacological applications for the CAAs [54]. Recently it has been unraveled that CAAs may be of great relevance in pathologies related to the pharmacological enhancement of synaptic efficacy, spatial learning, and memory, with the mechanistic details responsible for such phenomena reported by Blandina's group [54].…”
mentioning
confidence: 99%
“…However, up until recently there seem to be no pharmacological applications for the CAAs [54]. Recently it has been unraveled that CAAs may be of great relevance in pathologies related to the pharmacological enhancement of synaptic efficacy, spatial learning, and memory, with the mechanistic details responsible for such phenomena reported by Blandina's group [54]. Administration of CAAs of the amino acid type was shown to lead to an enhanced spatial learning, which was antagonized by the simultaneous administration of a sulfonamide inhibitor, such as acetazolamide [54].…”
mentioning
confidence: 99%
See 1 more Smart Citation